2014
DOI: 10.3171/2014.5.spine13600
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of minimally invasive and open spine surgery patient education resources

Abstract: Object The Internet has become a widespread source for disseminating health information to large numbers of people. Such is the case for spine surgery as well. Given the complexity of spinal surgeries, an important point to consider is whether these resources are easily read and understood by most Americans. The average national reading grade level has been estimated to be at about the 7th grade. In the present study the authors strove to assess the readability of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Previous studies on the readability of patient education materials for patients undergoing neurosurgical procedures, including those relevant to skull base tumors, have found similar results. [1][2][3]29 Future interventions aimed at improving the readability of patient education materials can have system-wide effects, given the ability of these resources to potentially lessen the need to treat preventable diseases across an array of medical subspecialties. Furthermore, this information can aid patients in better understanding the potential benefits and risks associated with various medical procedures, thereby increasing the likelihood that they will make informed decisions in the clinical setting (i.e., prior to any health intervention).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the readability of patient education materials for patients undergoing neurosurgical procedures, including those relevant to skull base tumors, have found similar results. [1][2][3]29 Future interventions aimed at improving the readability of patient education materials can have system-wide effects, given the ability of these resources to potentially lessen the need to treat preventable diseases across an array of medical subspecialties. Furthermore, this information can aid patients in better understanding the potential benefits and risks associated with various medical procedures, thereby increasing the likelihood that they will make informed decisions in the clinical setting (i.e., prior to any health intervention).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on evaluating the readability of patient education resources. [1][2][3][4][23][24][25][26][27][28][29] Understanding and proper utilization of these resources may require a level beyond the recommended fourth to sixth grade reading level. 3,4 This would leave patients at lower reading levels at a disadvantage.…”
mentioning
confidence: 99%
“…5,22 Previous studies have demonstrated that the FRE scores for neurosurgical patient education resources have been low, corresponding to increased difficulty of reading and perhaps lower quality. 1,2,4 This study evaluates the websites of the American Association of Neurological Surgeons (AANS), the University of Pittsburgh Medical Center (UPMC; Healthwise Inc.), and the National Institute of Neurological Disorders and Stroke (NINDS), focusing on the quality of patient education materials provided with regards to their accessibility, usability, and reliability.…”
mentioning
confidence: 99%
“…Image-guided minimally invasive spine surgery (IG-MISS) was wildly performed for the degenerated lumbar spine in the last decades [ 1 ]. The public demand has been increased for these procedures due to its various benefits, such as performing more accurate instrumentation placement with less radiation exposure, yielding less postoperative complications, and reducing recovery time [ 2 , 3 ]. In Image-guided-surgery (IGS) system, image segmentation of the interesting anatomical structure is an essential preprocessing step for 3D reconstruction and image registration, which is commonly applied in preoperative planning, intraoperative navigation, and postoperative assessment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%